Health impacts of the Northern Territory intervention - O’Mara, Peter (Medical Journal of Australia, 2010)
During 2006 and 2007, there was much discussion in the media about child sexual assault in Northern Territory Aboriginal communities. In April 2007, the report of the NT Board of Inquiry into the Protection of Aboriginal Children from Sexual Abuse, entitled Ampe akelyernemane meke mekarle “Little children are sacred”, was presented to the Chief Minister of the NT Government; it was released to the public in June 2007. The report addressed concerns about child sexual abuse and made recommendations that child abuse and child sexual abuse be designated as issues of urgent national significance by both the Australian and NT governments.1 On 21 June 2007, the then Minister for Families, Community Services and Indigenous Affairs, Mal Brough MP, announced, on behalf of the Australian Government, the Northern Territory Emergency Response (NTER) to protect Aboriginal children in the NT.2 The announcement included, among other measures, alcohol restrictions, welfare reform, compulsory income management, compulsory health checks, banning of pornography, scrapping of the permit system for common areas, and improving housing and community living arrangements. Significantly, legislation was passed by the Australian Parliament suspending Part II of the Racial Discrimination Act 1975 (Cwlth), so that the government’s measures could be imposed in prescribed Aboriginal communities in the NT.3 Part II of the Act prohibits racial discrimination in rights to equality before the law; access to places and facilities, land, housing and other accommodation; and provision of goods and services.
Keywords: Health impacts; Northern Territory intervention